Prognostic factors for the outcome of nonfunctioning pancreatic neuroendocrine tumors in MEN1: a systematic review of literature. Issue 6 (June 2020) - Sadowski, S M; Pieterman, C R C; Perrier, N D; Triponez, F; Valk, G D
Abstract : Metastatic duodenopancreatic neuro-endocrine tumors (dpNETs) are the most important disease-related cause of death in patients with multiple endocrine neoplasia type 1 (MEN1). Nonfunctioning pNETs (NF-pNETs) are highly prevalent in MEN1 and clinically heterogeneous. Therefore, management is controversial. Data on prognostic factors for risk stratification are limited. This systematic review aims to establish the current state of evidence regarding prognostic factors in MEN1-related NF-pNETs. We systematically searched four databases for studies assessing prognostic value of any factor on NF-pNET progression, development of distant metastases, and/or overall survival. In- and exclusion, critical appraisal and data-extraction were performed independently by two authors according to pre-defined criteria. Thirteen studies (370 unique patients) were included. Prognostic factors investigated were tumor size, timing of surgical resection, WHO grade, methylation, p27/p18 expression by immunohistochemistry (IHC), ARX/PDX1 IHC and alternative lengthening of telomeres. Results were complemented with evidence from studies in MEN1-related pNET for which data could not be separately extracted for NF-pNET and data from sporadic NF-pNET. We found that the most important prognostic factors used in clinical decision making in MEN1-related NF-pNETs are tumor size and grade. NF-pNETs <2 cm may be managed with watchful waiting, while surgical resection is advised for NF-pNETs ≥2 cm. Grade 2 NF-pNETs should be considered high risk. The most promising and MEN1-relevant avenues of prognostic research are multi-analyte circulating biomarkers, tissue-based molecular factors and imaging-based prognostication. Multi-institutional collaboration between clinical, translation and basic scientists with uniform data and biospecimen collection in prospective cohorts should advance the field.